Accounting for Capitalized Leases: Tax Considerations. - Bierman, Harold (The Accounting Review, 1973)
The article discusses tax considerations in relation to accounting for capitalized leases. The example given in the article assumed that a capitalized lease was considered appropriate. A zero tax rate was generally assumed by the accounting entries for leasing. Eliminating such assumption would lead to a more complex analysis, but the before tax and after tax computations could be reconciled. The lease problem illustrated in the article was a good example of the fact that one could not always assume that the after tax accounting analysis of a situation was a simple extension of the no tax situation.